2017
DOI: 10.1002/wcms.1350
|View full text |Cite
|
Sign up to set email alerts
|

State‐to‐state photodissociation dynamics of the water molecule

Abstract: Photodissociation provides an ideal proving ground for an in‐depth understanding of the microscopic mechanism and dynamics of bond breaking processes at a state‐to‐state level. After a brief outline of the requisite theory, we review the latest developments on the state‐to‐state photodissociation dynamics of the water molecule via the lowest two excited states, focusing on the absorption spectrum and product state distributions. A detailed discussion is given on the competition between different adiabatic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 152 publications
(414 reference statements)
1
22
0
Order By: Relevance
“…H 2 O (HOD, D 2 O) is probably the most studied triatomic molecule both experimentally and theoretically, and its importance can never be overstated. Detailed thorough experimental and theoretical reviews on the photodissociation dynamics of H 2 O (HOD, D 2 O) have been made recently by Yang [58] and Xie [59], respectively, thus readers should refer to these two review articles and the references therein for more details, we will only make a brief summary on the most recent experimental progress and some future prospects on the photodissociation studies of H 2 O (HOD, D 2 O). HRTOF and TPR-FWM generated VUV sources have been the main tools for experimentally investigating the stateto-state photodissociation dynamics of H 2 O, HOD and D 2 O into the channels H/D+OH/OD.…”
Section: A H 2 O (Hod D 2 O)mentioning
confidence: 99%
“…H 2 O (HOD, D 2 O) is probably the most studied triatomic molecule both experimentally and theoretically, and its importance can never be overstated. Detailed thorough experimental and theoretical reviews on the photodissociation dynamics of H 2 O (HOD, D 2 O) have been made recently by Yang [58] and Xie [59], respectively, thus readers should refer to these two review articles and the references therein for more details, we will only make a brief summary on the most recent experimental progress and some future prospects on the photodissociation studies of H 2 O (HOD, D 2 O). HRTOF and TPR-FWM generated VUV sources have been the main tools for experimentally investigating the stateto-state photodissociation dynamics of H 2 O, HOD and D 2 O into the channels H/D+OH/OD.…”
Section: A H 2 O (Hod D 2 O)mentioning
confidence: 99%
“…The EOMIP-CCSD curve [148] predicted a significant barrier which is about 5 kcal/mol above the trans minimum and then drops steeply to reach the asymptote at 2.5 kcal/mol. The existence of such a barrier 13.8 1.472 G2M2(RCC) [144] 1.3 1.543 MRMP2//CASSCF [117] 6.0 2.8 1.750 QCISD(T)-CBS [145] 5.3 1.495 CCSD(T)-CBS(W1U) [122] 3.4 0.1 1.544 MRCIQ+Q [136] 3.9 1.677 CCSD(T)//QCISD [146] 0.1 −3.9 1.522 MRCI+Q [146] 5.4 1.4 1.647 MRCI+Q//CASSCF [139] 3.5 1.544 MRCI+Q/VTZ [147] 1.695 HCTH [139] 9.9 6.2 1.610 CCSD(T) [148] 5.2 2.5 1.589 CCSD(T)-CBS [149] 1.582 CASPT2 (13,11) [150] 5.4 2.6 1.734 CASPT2 (19,15) [150] 5.8 3.0 1.682 MRCI+Q/VQZ [151] 4.7±0.1 2.7±0.2 1.691 Expt. [154] 2.9±0.07 Expt.…”
Section: The Ho3 Systemmentioning
confidence: 99%
“…Due to the quantum mechanical nature of the motion of electron and nucleus, only quantum treatments can provide the definitive characterisation of the reaction dynamics. The quantum dynamical theories have achieved great success during the past 40 years [1][2][3][4][5][6][7][8][9][10][11] since the first quantum state-resolved dynamical calculation for the simplest H+H 2 system was carried out [1]. Quantum state-resolved dynamical study can provide the most detailed microscopic mechanism for chemical reactions and has become a major tool for understanding the multi-dimensional dynamics, tunneling, isotopic effect, mode selectivity, nonadiabatic effect, and reaction resonance state.…”
Section: Introductionmentioning
confidence: 99%
“…products. [17][18][19][20][21][22][23][24][25][26][27][28][29] The next two excited states identified in absorption have predominant Rydberg character, and predissociate by non-adiabatic coupling to those lower (predominantly valence) states. The C 1 B1 state shows resolvable rotational structure at  ~124 nm, [30][31][32][33] and previous studies have identified dramatic variations in the OH product state distributions and angular distributions that arise following excitation to different rotational levels of this state.…”
Section: Introductionmentioning
confidence: 99%